2018
DOI: 10.1177/0361684318793848
|View full text |Cite
|
Sign up to set email alerts
|

“I’m Not a Science Nerd!”

Abstract: Stereotypes reduce women's identification with science, technology, engineering, and math (STEM), which can decrease their motivation to enter STEM domains. Stereotypes may be gender-based (e.g., STEM is for men) or trait-based (e.g., STEM is for geniuses). In this study, I explored two primary research questions: First, would stereotyping STEM as a domain for nerdy geniuses negatively relate to women's STEM identity? Second, would STEM identity mediate the relation between stereotypes and STEM motivation? Ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 81 publications
(130 reference statements)
3
57
1
3
Order By: Relevance
“…Consistent with Starr's (2018) rationale for assessing STEM typicality, Carlone and Johnson (2007) made the strong case that students from under-represented groups in science fields may be especially likely to struggle with feeling that they are recognized by others as belonging to a field of science professionals. In their qualitative analysis of science identity, Carlone and Johnson proposed that, in order for individuals to have a strong science identity, they must feel (1) confident that they have (or are capable of acquiring) the knowledge necessary to understand science concepts (i.e., competence), (2) confident in their ability to showcase their science skills in public settings (i.e., performance), and (3) that othersparticularly those within the scientific community-recognize their competence and performance (i.e., recognition).…”
Section: What Is Science Identity?mentioning
confidence: 88%
See 3 more Smart Citations
“…Consistent with Starr's (2018) rationale for assessing STEM typicality, Carlone and Johnson (2007) made the strong case that students from under-represented groups in science fields may be especially likely to struggle with feeling that they are recognized by others as belonging to a field of science professionals. In their qualitative analysis of science identity, Carlone and Johnson proposed that, in order for individuals to have a strong science identity, they must feel (1) confident that they have (or are capable of acquiring) the knowledge necessary to understand science concepts (i.e., competence), (2) confident in their ability to showcase their science skills in public settings (i.e., performance), and (3) that othersparticularly those within the scientific community-recognize their competence and performance (i.e., recognition).…”
Section: What Is Science Identity?mentioning
confidence: 88%
“…This approach to social identity can be broadly construed as identity centrality (Leach et al, 2008). However, other research has suggested that social identity is multi-faceted, and includes a facet of typicality (referred to as self-stereotyping by Leach et al, 2008;Starr, 2018). This perspective recognizes that two elements are essential for developing a social identity: (1) seeing oneself as a member of the group, and (2) feeling that the members of the group accept you as a member (Kim et al, 2018).…”
Section: What Is Science Identity?mentioning
confidence: 99%
See 2 more Smart Citations
“…We suppose that these results manifest two currently widespread gender stereotypes. One of them is associated with the ideas about intellectual superiority of males compared with females (Gálvez et al 2019;Starr 2018).…”
Section: Discussionmentioning
confidence: 99%